2020
DOI: 10.1149/1945-7111/ab6974
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Composite Additive on Gold Electrodeposition in DMH-Based Electrolyte: Combined Experimental and Theoretical Study

Abstract: The comparison of macroscopic appearance and microscopic morphology of gold electrodeposit determined PHEN as the main brightener for its effective influence on refining the grains, resulting in a golden bright and shiny deposit. Improving the flatness of deposit when used together with PHEN, PDDA was the auxiliary brightener, thereby obtaining thicker deposits. Results of TEM and XRD showed that the average size of refined gold crystals was about 20 nm. We speculated from the patterns of XPS that the action o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Contact angle measurements indicated that the electrolytes with EDTA had an enhanced affinity for Zn (Figure e). DFT calculations also revealed that the functional groups of EDTA endowed the EDTA on the Zn foil with a good adsorption capability (Figure f), thus ensuring an abundance of activated sites that would contribute to the generation of refined nucleation grains with good uniformity . Moreover, foreign adsorbed molecules on the surface of electrode can improve the activation energy for adatoms diffusion, thus restraining the 2D surfacial ion diffusion, which may lead to dendrite growth …”
Section: Resultsmentioning
confidence: 99%
“…Contact angle measurements indicated that the electrolytes with EDTA had an enhanced affinity for Zn (Figure e). DFT calculations also revealed that the functional groups of EDTA endowed the EDTA on the Zn foil with a good adsorption capability (Figure f), thus ensuring an abundance of activated sites that would contribute to the generation of refined nucleation grains with good uniformity . Moreover, foreign adsorbed molecules on the surface of electrode can improve the activation energy for adatoms diffusion, thus restraining the 2D surfacial ion diffusion, which may lead to dendrite growth …”
Section: Resultsmentioning
confidence: 99%
“…The intricate electrochemical reactions led to the adsorption of S 2 O 5 2– and S 2 O 3 2– on the cathode. Tu et al pointed out that the interfacial adsorbate significantly affected the morphology, appearance of coating, and the performance of the bath during the metal ions electroreduction. It can be clearly seen that the adsorption of S 2 O 5 2– and S 2 O 3 2– will influence the quality of coating in metal (such as gold) sulfite electrodeposition.…”
Section: Introductionmentioning
confidence: 99%
“…the cathode. Tu et al26 pointed out that the interfacial adsorbate significantly affected the morphology, appearance of coating, and the performance of the bath during i v i d u a l n o t d i r e c t l y a s s o c i a t e d w i t h s c i t e i s p r o h i b i t e d . the metal ions electroreduction.…”
mentioning
confidence: 99%